PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KONVEKSI TEMUROSE KECAMATAN BLULUK KABUPATEN LAMONGAN - Moh Rivqi Amin; Rizki Hidayaturrochman (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to examine and analyze the influence of leadership style, motivation, and work discipline on employee performance at Temurose Convection in Bluluk Subdistrict, Lamongan Regency. The hypothesis of this research is that leadership style, motivation, and work discipline simultaneously influence employee performance. Data collection was carried out by distributing questionnaires to 35 employees of Temurose Convection. Data analysis in this study utilized SPSS version 16. The sampling technique used was non-probability sampling. Data analysis techniques included validity tests, reliability tests, multiple linear regression analysis, multiple correlation analysis, and determination analysis. Hypothesis testing was performed using the F-test and t-test. The results of the multiple linear regression analysis yielded the equation: Y= 1,1516-0,270X_1+ 0,275X_2+0,384X_3. The F-test results indicated that leadership style, motivation, and work discipline simultaneously have a significant effect on employee performance. The t-test results showed that the leadership style variable has a partial influence on employee performance. The analysis concluded that leadership style positively affects employee performance, motivation positively affects employee performance, and work discipline also positively affects employee performance.